(3QSGdI aj QShe GdNW GdeSJbjes - (3GbdjOSs
(3ChdgG (B:s
(3GdNW GdeSJbje dg QShe CMOgG bhd EbdjOS (B: (3hgh Gfg GdehVhY Ydi ebGHdgG Ci fbWI cGfJ Ydjg HYVgG dHYV s
(3BNQgG (B:s
(3hNGeSgG gh GdPi jSJQ hSWg WQajg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs